‘I am almost the middle-class white man, aren’t I?’: elite women, education and occupational trajectories in late twentieth-century Britain - Worth, E; Reeves, A (Taylor & Francis, 2023)
This paper makes a major intervention in the historiography of elites through analysis of the experience of women occupational elites born in post-war Britain. The paper draws on a new set of oral history interviews recently conducted with women born in the post-war decades with an entry in Who’s Who which is the leading biographical dictionary of ‘noteworthy and influential’ people in the UK. The women we interviewed were all highly occupationally successful and those analysed here also attended one of twelve elite girls’ schools. This article argues that our interviewees can be separated into two distinct post-war cohorts: one born between early 1940s and mid-1950s and the other born late 1950s to late 1960s. The shape and structure of the cohort’s trajectories were different, their relationship to their careers were different, and, even though both groups faced sexual discrimination and unequal divisions of labour, the nature of these gendered inequalities changed too. By foregrounding elite women within this shifting historical context, this article illuminates broader trends in both classed and gendered experience and how this related to the changing nature of the economy in recent history.